Amino acid identification and protein content determination of Locusta migratoria manilensis Meyen (Family Locustidae) - Smith, Allan T.; Jadulco, Racquel C. (Manila Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 1995)
The total Nitrogen content of dried Locusta migratoria was determined using Kjeldahl method. Three determinations were made and the values obtained were 6.65%, 5.91%, and 8.91%, giving an average of 7.15%. The percentage deviation for each trial was 6.99%, 17.34% and 24.62%, respectively. The non-protein Nitrogen content (NPN) was also determined and the values obtained were: 1.90% and 1.71%, giving an average of 1.80%. The percent deviation for each trial was 5.56% and 5.00%, respectively. The average NPN content was subtracted from the total Nitrogen content and the result was multiplied by 6.25 to get the percentage protein content. The value obtained was 33.43%.
A protein isolate was produced from the dried locusts by extraction with dilute NaOH at pH 11, precipitation with 15% trichloroacetic acid (TCA), separation by centrifuge and subsequent freeze drying. The resulting product was hydrolysed with 6 N HCl at 110oC for 35 h. The amino acid present were identified using paper chromatography.
Only 13 amino acids (alanine, aspartic acid, cystine, cysteine, glycine, histidine, leucine, methionine, phenylalanine, serine, tryptophan, threonine, and tyrosine) were identified because of unavailability of some amino acid standards in the laboratory. The moisture content was found to be 8.0% using a moisture determining balance model AD-4712 from the A&D Co., Ltd.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, [1995].
Keywords: Grasshoppers; Migratory locust; Amino acids; Balang